Dietary Thiamin and Riboflavin intake and blood Thiamin and Riboflavin concentrations in collegiate swimmers under intensive training - Sato, A.; Shimoyama, Y.; Ishikawa, T.; Murayama, N. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The purpose of this study was to provide quantified data to find relationship between high physical activity by swimming training and biochemical thiamin and riboflavin status. METHODS: Thiamin and riboflavin concentrations in the whole blood of a group of 19 collegiate swimmers (6 males and 13 females) were measured during a low-intensity preparatory period and compared with measurements taken during a high-intensity training period. Additional variables included anthropometric characteristics; estimated energy expenditure during swimming training; distance covered; resting energy expenditure; estimated energy requirement per day; and dietary intake of energy, thiamin, and riboflavin. RESULTS: No major changes were observed in anthropometric characteristics or dietary intake, while energy expenditure during swimming training per day significantly increased in the intensive training period (496 ± 0 kcal in the preparation period versus 995 ± 96 kcal in the intensive training period for males [P < 0.001] and 361 ± 27 kcal versus 819 ± 48 kcal, respectively, for females [P < 0.001]). Blood thiamin concentration decreased significantly during the intensive training period compared to the preparation period (41 ± 6 ng/mL decreased to 36 ± 3 ng/mL for males [P = 0.048], and 38 ± 10 ng/mL decreased to 31 ± 5 ng/ mL for females [P = 0.004]); however, the concentration of riboflavin was unchanged. DISCUSSION: Thiamin is more sensitive to an increase in carbohydrate metabolism whereas riboflavin is more sensitive to changes in fat metabolism. Because the percentage of carbohydrates utilized as an energy resource increases along with the increase in intensity of physical activity, blood thiamin concentration is considered more sensitive than riboflavin concentration to an increase in energy expenditure brought about by intense training.